الدّرس النّقدي المغاربي القديم "مقاربة وصفيّة تحليليّة للمصطلحات والقضايا" عبد الكريم النّهشلي –نموذجا- - بوعزة, عبد الفتاح (جامعة الوادي - University of Eloued, 2022)
مثّل الدّرس النّقديّ المشرقيّ القديم فضاء، من فضاءات تشكّل ظاهرة الشّعر؛حيث كانت الشّغل الشّاغل لدى جمهرة كبيرة من نقّاد العرب؛ لتتضارب آراؤهم، وتتقارب، وتتباعد في تفسير الشّعر ظاهرة ومفهوم؛انطلاقا من أسباب نشأته،ودواعيه،وأطره الدّاخليّة والخارجيّة الّتي تحكمه، كما كان لقضيّة اللّفظ والمعنى دورا فعّالا في إذكاء نار الجدل؛ من خلال تغليب اللّفظ على المعنى أو العكس، وفي جانب آخر هناك من دعا إلى فضّ النّزاع بينهما وجعلهما وجهين للعملة ذاتها؛هذا بالنّسبة للنّقد المشرقي فكيف كان حضور هذين القضيّتين في الدّرس المغاربي القديم عند "عبد الكريم النّهشلي -نموذجا-" ؟ باعتباره أحد أهم النقّاد المغاربة الذين عالجوا هذين القضيّتين من خلال كتابه " الممتع في صناعة الشّعر"؟ The ancient Oriental literary criticism lesson has represented a valuable space for the shaping of poetry. It has been the preoccupation of a number of Arab critics who showed diversity of opinions in their attempt to interpret poetry as a phenomenon and a concept, starting from the causes and aims of its appearance, as well as its internal and external contexts. The debate over word and meaning has a deep impact on heightening the controversy through emphasizing word over meaning and vice versa. On the other hand, some critics have suggested a compromise between both divides. This is true for Oriental literary criticism. The question to be raised, however, is the presence of these issues in the ancient Maghrebian literary criticism lesson through the works of Abdulkarim Al-Nahshaly. The latter is considered to be one of the most important Maghrebian critics who dealt with these two issues in his book Al-Mumtae fi Sinaeat Al-Shiaer
مقال
Keywords: النقد المغاربي، الشعر،اللفظ، المعنى، عبد الكريم النهشلي; Maghreb criticism, poetry, pronunciation, meaning, Abdel